Therapeutic Induction of Tertiary Lymphoid Structures in Cancer Through Stromal Remodeling - Johansson-Percival, Anna; Ganss, Ruth (Frontiers in Immunology, 2021)
Improving the effectiveness of anti-cancer immunotherapy remains a major clinical challenge. Cytotoxic T cell infiltration is crucial for immune-mediated tumor rejection, however, the suppressive tumor microenvironment impedes their recruitment, activation, maturation and function. Nevertheless, solid tumors can harbor specialized lymph node vasculature and immune cell clusters that are organized into tertiary lymphoid structures (TLS). These TLS support naïve T cell infiltration and intratumoral priming. In many human cancers, their presence is a positive prognostic factor, and importantly, predictive for responsiveness to immune checkpoint blockade. Thus, therapeutic induction of TLS is an attractive concept to boost anti-cancer immunotherapy. However, our understanding of how cancer-associated TLS could be initiated is rudimentary. Exciting new reagents which induce TLS in preclinical cancer models provide mechanistic insights into the exquisite stromal orchestration of TLS formation, a process often associated with a more functional or “normalized” tumor vasculature and fueled by LIGHT/LTα/LTβ, TNFα and CC/CXC chemokine signaling. These emerging insights provide innovative opportunities to induce and shape TLS in the tumor microenvironment to improve immunotherapies.